The Effect of Sonication Time on the Properties of Electrically Conductive PANI/Sago Starch Blend Prepared by the One-Pot Synthesis Method - Ali Mohsin, M. E.; Shrivastava, Nilesh K.; Basar, Norazah; Arsad, Agus; Hassan, Azman (Frontiers in Materials, 2019)
This study is part of on-going research on preparation of electrically conductive and physically stable Polyaniline/Sago starch (PANI/Sago) blend films using simple one-pot synthesis method. The synthesis of PANI in presence of Sago to prepare PANI/Sago blend was done via in-situ polymerization using ultrasound irradiation. For in-situ polymerization of PANI/Sago blends, ammonium persulfate (APS) was used as oxidant while hydrochloric acid (HCl) acted dopant. The effect of sonication time (0.5 to 5 hrs) on the structural properties (1H NMR and FT-IR), electrical conductivity (E.C), optical properties (UV-VIS), morphological (FE-SEM) and thermal properties (TGA) of the prepared PANI/Sago blends was studied. 1H NMR and FT-IR results reveals that, polymerization of PANI/Sago for more than 2 hrs leads to disintegration/deformation of sago starch due to excessive kinetic energy generated via continuous collapsing of cavitation bubbles. In addition to the findings about sago starch, FT-IR analysis also reveals the dominance of PANI property for the blend sonicated for 2 hrs, as it contains sharp and intense PANI peak at 1500 cm-1 which represents the stretching vibration of benzenoid ring. 1H NMR and FT-IR results were found to be in compliance with E.C results, which showed the E.C of the blend sonicated for 2 hrs was highest. The UV-Vis results in combination with energy band values supported the E.C results. The morphology of the prepared blends was found to be highly connected which helps in good inter and intra-chain electron transfer within the blends. The variation in sonication time seems to have very little impact, as it was found that all blends were thermally stable up to 200 oC.